Intestinal Bacterial Colonization in the First 2 Weeks of Life of Nigerian Neonates Using Standard Culture Methods - Kigbu, Allan; Orimadegun, Adebola E.; Tongo, Olukemi O.; Odaibo, Georgina N.; Olaleye, David O.; Akinyinka, Olusegun O. (Frontiers in Pediatrics, 2016)
Objective: The pattern and timing of development of intestinal microflora in Nigerian infants have been scarcely researched. This study was carried out to investigate the bacteria flora in the rectum of healthy neonates in Ibadan, Nigeria. Patients and Methods: In this hospital-based longitudinal study, rectal swabs of 70 neonates were taken within 6-12 hours of birth(day 1) and subsequently on days 3, 9 and 14.Information collected included maternal socio-demographic characteristics, antibiotic use for the neonates and type of feeding during the first 14-days of life. Identification and speciation of gram negative isolates were done using the Analytical Profile Index 20E® and 20NE® as appropriate. Gram-positive bacteria were identified biochemically using the catalase and coagulase tests. Data were analysed using descriptive statistics and Chi square at p = 0.05. Results: Majority (92.9%) of the neonates were delivered vaginally with a median gestational age of 38 weeks (range = 34-42). On the first day of life, Escherichia coli was isolated more frequently from the rectal swabs of preterm (50.0%) than term (23.1%) neonates (p=0.031). On day 3 of life, Coagulase-negative Staphylococci was the most frequently isolated bacteria from the rectal swabs of non-asphyxiated (64.4%) compared with asphyxiated (27.3%) neonates’ rectal swabs (p=0.042). Staphylococcus aureus was the most frequently isolated bacteria from the rectal swabs of non-exclusively breastfed (66.7%) than exclusively breastfed (21.3%) neonates on day-14 (p=0.004). Conclusion: Staphylococcus aureus and Escherichia coli were the predominant isolates from the rectum of Nigerian neonates and these isolates were influenced by breastfeeding and mild-moderate asphyxia. In all, bacterial diversity in the rectum increased as the neonates got older.